2013
DOI: 10.1007/s10735-013-9548-x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical examination of cathepsin K, MMP1 and MMP2 in compressed periodontal ligament during orthodontic tooth movement in periostin deficient mice

Abstract: The purpose of this study was to investigate immunolocalization of collagenolytic enzymes including cathepsin K, matrix metalloproteinase (MMP) 1 and 2 in the compressed periodontal ligament (PDL) during orthodontic tooth movement using a periostin deficient (Pn-/-) mouse model. Twelve-week-old male mice homozygous for the disrupted periostin gene and their wild type (WT) littermates were used in these experiments. The tooth movement was performed according to Waldo's method, in which elastic bands of 0.5 mm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…Our previous study demonstrated that periostin plays an essential role in the function of collagenolytic enzymes such as cathepsin K, MMP1 and MMP2 in the compressed PDL after orthodontic force application. This aided the degradation of collagen fibers and facilitating orthodontic force-induced tooth movement, while deficiency of periostin inhibited the elimination of collagen fibers and obstructed the corresponding tooth movement (Lv et al 2014b). In this study, we obtained similar results showing that both groups exhibited extensive formation of cell-free hyaline zones at the PDL of the compression side and the PDL at this side was less compressed in Pn-/-mice than in WT mice.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our previous study demonstrated that periostin plays an essential role in the function of collagenolytic enzymes such as cathepsin K, MMP1 and MMP2 in the compressed PDL after orthodontic force application. This aided the degradation of collagen fibers and facilitating orthodontic force-induced tooth movement, while deficiency of periostin inhibited the elimination of collagen fibers and obstructed the corresponding tooth movement (Lv et al 2014b). In this study, we obtained similar results showing that both groups exhibited extensive formation of cell-free hyaline zones at the PDL of the compression side and the PDL at this side was less compressed in Pn-/-mice than in WT mice.…”
Section: Discussionsupporting
confidence: 64%
“…Specially, Wolf et al (2013c) reported the peak expression of HMGB1 in periodontal ligament cells following 3 days of mechanical loading. Furthermore, our previous study showed the fully formed cell free hyaline zones in PDL of the compression side at day 3 after the application of mechanical stress using Waldo's method (Lv et al 2014b). There is no significant difference between the mesial and distal PDL surrounding the root (e).…”
Section: Discussionmentioning
confidence: 97%
“…Only the hyalinized tissue at the compression side be eliminated by macrophages can osteoclasts be recruited and formed here to perform bone resorption which makes further orthodontic tooth movement possible (Kurol and Owman-Moll 1998). Otherwise, further tooth movement would be obstructed if the secretion of matrix degradation-associated enzymes such as cathepsin K, MMP1 and MMP2 by macrophages or osteoclasts is disturbed, just as reported by our previous study (Lv et al 2014).…”
Section: Discussionmentioning
confidence: 58%
“…Previously we reported that the expression of cathepsin K, matrix metalloproteinase 1 (MMP1), and MMP2 was significantly decreased in the periodontal ligament of periostin −/− mice compared with that in their wildtype counterparts (Lv et al 2014), suggesting that periostin was required for the expression of these enzymes. CCN3 has been demonstrated to play roles in the expression of MMPs (Laurent et al 2003;Benini et al 2005;Lin et al 2005;Fukunaga-Kalabis et al 2008;Tzeng et al 2011;Kular et al 2012).…”
Section: Discussionmentioning
confidence: 99%